The Influence of Organizational Culture, Democratic Leadership Style, and Work Motivation on Employee Work Discipline at the Industry and Manpower Office of Temanggung Regency - Yoga Aji Pratama (Economics and Digital Business Review, 2026)
Employee work discipline is crucial for achieving organizational goals. This study aims to determine the influence of organizational culture, democratic leadership style, and work motivation on employee work discipline, both partially and simultaneously, at the Industry and Manpower Office of Temanggung Regency. This study used a quantitative approach. The sample consisted of 50 employees using a census technique. The results showed that partially, organizational culture had a significant positive effect on work discipline (t-value 3.161, sig. 0.003). Meanwhile, democratic leadership style (sig. 0.789) and work motivation (sig. 0.325) did not have a significant effect on work discipline. However, simultaneously, all three variables had a positive and significant effect on employee work discipline (F-value 19.194, sig. 0.001). The Adjusted R Square value of 0.527 indicates that 52.7% of the variation in work discipline is explained by the three independent variables. In conclusion, culture drives discipline, not democratic leadership or motivation alone, yet together they still have impact